Contingent Existence and the Reduction of Modality to Essence. Issue 509 (9th November 2017) - Teitel, Trevor
Abstract: This paper first argues that we can bring out a tension between the following three popular doctrines: (i) the canonical reduction of metaphysical modality to essence, due to Fine, (ii) contingentism, which says that possibly something could have failed to be something, and (iii) the doctrine that metaphysical modality obeys the modal logic S5. After presenting two such arguments (one from the theorems of S4 and another from the theorems of B), I turn to exploring various conclusions we might draw in light of these results, and argue that none comes cost-free. In the course of laying out possible responses to my arguments, we'll have a chance to evaluate various doctrines about the interplay between contingency and essence, as well as develop some alternative reductions of metaphysical modality to essence. I don't come down decisively in favour of one response over the others, though I say some things that point towards the conclusion that essence has no role to play in reducing metaphysical modality.